PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK ( LKPD ) BERBASIS SRTUCTURED NUMBERED HEADS PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) - Erna, Maria; ', Ristiana; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The student activities sheet based on structured numbered heads for chemistry grade XI senior high school in solubilty and solubility product materials has been developed. Method of this research is Research and Development (R & D). The instruments of this research are questioners which are given to the validators. There are three validators, two of validators is lecturer in chemistry university of riau and one validator are teachers of SMAN 12 Pekanbaru. The result of this research shows the validity of student participant exercise sheet is 3,56 or 89 %, and category of validity is very high. Based on the result analysis can be concluded that the learning device consist of student activities sheet based on structured numbered heads for chemistry grade XI senior high school in solubilty and solubility product materials has been valid and proper.Keywords: development, SNH, validation